Effect of in vitro growth on mouse oocyte competency, mitochondria and transcriptome. Issue 4 (9th September 2021) - Takashima, Tomoya; Fujimaru, Tsubasa; Obata, Yayoi
Abstract : In vitro generation of fertile oocytes has been reported in several mammalian species. However, oocyte integrity is compromised by in vitro culture. Here, we aimed to understand the factors affecting oocyte competency by evaluating mitochondrial function and transcriptome as well as lipid metabolism in in vivo -derived oocytes and in vitro grown and matured (IVGM) oocytes under atmospheric (20%) and physiological (7%) O2 concentration. We used single-cell RNA-sequencing as well as Gene Ontology and KEGG analyses to identify the molecular pathways affecting the developmental competence of oocytes. Oocytes grown under 20% O2 conditions showed a significant decrease in mitochondrial membrane potential, upregulation of ceramide synthesis pathway-associated genes, and high ceramide accumulation compared with oocytes grown under 7% O2 conditions and in vivo -grown oocytes. This suggests that excess ceramide level causes mitochondrial dysfunction and poor developmental ability of the oocytes. Mitochondrial DNA copy number was lower in IVGM oocytes irrespective of O2 concentration in culture, although there was no common abnormality in the expression of genes related to mitochondrial biosynthesis. In contrast, some oocytes produced under 7% O2 conditions showed gene expression profiles similar to those of in vivo -grown oocytes. In these oocytes, the expression of transcription factors, including Nobox, was restored. Nobox expression correlated with the expression of genes essential for oocyte development. Thus, Nobox may contribute to the establishment of oocyte competency before and after the growth phase. The comprehensive analysis of IVGM oocytes presented here provides a platform for elucidating the mechanism underlying functional oocyte production in vivo .